People in the civil service an evaluation of their performance - Dans, Albina M. (1977)
The Civil Service Commission (CSC) through its Performance Evaluation Program aims to determine the efficacy and capability of government personnel in responding to its new functions and to provide a tool for employee development. In order to implement this program covering the different branches of the national and regional government, the CSC organized: (a) Performance Evaluation Committees composed of government officers, members of the academe, and selected individuals and (b) a Civil Service Staff in each department, office or agency which shall serve as the liaison between the Commission and these offices. The Program is an effort to awaken employees' consciousness and interest to improve their performance in the public service.
Keywords: Civil service -- Evaluation; Civil Service Commission; Public administration; Personnel management